2006
DOI: 10.1103/physrevb.74.085112
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional diagonal order and three-dimensional stacking of charge stripes in orthorhombicPr1.67Sr0.33NiO4andet al.

Abstract: The interplay between crystal symmetry and charge stripe order in Pr 1.67 Sr 0.33 NiO 4 and Nd 1.67 Sr 0.33 NiO 4 has been studied by means of single crystal x-ray diffraction. In contrast to tetragonal La 1.67 Sr 0.33 NiO 4 , these crystals are orthorhombic. The corresponding distortion of the NiO 2 planes is found to dictate the direction of the charge stripes, similar to the case of diagonal spin stripes in the insulating phase of La 2−x Sr x CuO 4 . In particular, diagonal stripes seem to always run along … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…This has not yet been detected in stripe-ordered LSNO, where the correlation length remains finite; however, stripes choose a unique orientation in orthorhombic R 1.67 Sr 0.33 NiO 4 with R ¼ Pr, Nd (ref. 18)). The charge-stripe period in real space equals a/(2d).…”
Section: General Considerationsmentioning
confidence: 99%
“…This has not yet been detected in stripe-ordered LSNO, where the correlation length remains finite; however, stripes choose a unique orientation in orthorhombic R 1.67 Sr 0.33 NiO 4 with R ¼ Pr, Nd (ref. 18)). The charge-stripe period in real space equals a/(2d).…”
Section: General Considerationsmentioning
confidence: 99%
“…3B) by a model with ABAB stacking of the stripes along c, akin to that shown in figure 10B in ref. 18. Note that this ABAB stacking sequence permits even l reflections and thus, differs from the LSNO-1/3 stacking pattern in which bondand site-centered stripes alternate along c, for which odd l reflections only are observed.…”
Section: Resultsmentioning
confidence: 99%
“…The real space pattern of charge order varies by material (6-9), but a typically observed motif is some variety of charge stripes. Such stripes have been observed in cobaltites (10-12), cuprates (13-15), nickelates (16)(17)(18)(19), and manganites (20-22), albeit with highly materials-dependent configurations that hinge on a balance among Coulomb, lattice, and magnetic exchange energies. For instance, charge stripes in layered nickelates typically stagger themselves from layer to layer to reduce the collective electrostatic energy arising from the charge disproportionation (9, 18).…”
mentioning
confidence: 99%
“…This can be achieved by studying Nd 2−x Sr x NiO 4 , which has the same low-temperature orthorhombic structure as La 2 CuO 4 , with inequivalent lattice parameters along the diagonals. A careful x-ray diffraction study by Hücker et al [119] on crystals with x = 0.33 demonstrated that the charge stripes run uniquely along the shorter a axis.…”
Section: Nickelatesmentioning
confidence: 99%